Plastic versus metal stents for transmural drainage of walled-off necrosis with significant solid debris: a randomized controlled trial - Kakadiya, Rinkal; Muktesh, Gaurav; Samanta, Jayanta; Mandavdhare, Harshal S; Gupta, Pankaj; Shah, Jimil; Sarma, Phulen; Gupta, Vikas; Yadav, Thakur Deen; Jena, Anuraag; Sharma, Vishal; Kochhar, Rakesh (Endoscopy International Open, 2023)
Background and study aims Recently, larger-caliber metal stents have been increasingly used, resulting in higher efficacy in walled-off necrosis (WON) with more solid debris. However, none of the trials have included WON with significant solid debris. The aim of this study was to compare plastic stents and metal stents for drainage of symptomatic WON with significant solid debris (≥20%).Patients and methods We conducted a single-center, open-label, noninferiority trial including 48 patients. The primary endpoint was treatment success. Secondary outcomes were technical success, total number of procedures, adverse events (AEs), duration of procedure, and treatment failure. All the outcomes were assessed at 3 weeks after drainage. Patients were followed up for 3 months to assess recurrence.Results Treatment succeeded in 21 of 24 patients (87.5%) and 20 of 24 patients (83.3%) in the metal and plastic stent groups, respectively with P=1.05 (95% confidence interval 0.81–1.39). Assuming 10% non-inferiority margin, P<0.001 for non-inferiority, suggesting that plastic stents are non-inferior to metal stents. The technical success rate was 100%. Procedure duration was significantly shorter in the metal stent group (12.95±5.3 minutes versus 29.77±6.6 minutes, P<0.001). The number of total procedures was comparable (2.8±1 vs 2.2±1, P=0.097). There were more minor AEs in plastic stent arm but no significant difference between the two groups. A single asymptomatic recurrence was observed in the metal stent arm.Conclusions Plastic stents are not inferior to metal stents for WON drainage with significant solid debris. However, larger sample-size studies are needed to make definite conclusions.
Keywords: Endoscopic ultrasonography; Pancreas; Intervention EUS